Analysis of Language Style in the Poem of the Fakir Session of the Word by Hamzah Fansuri - Khairani Muhammad; Suminto A Sayuti (BIRCU, 2023)
That language style is the author's way of conveying/expressing thoughts through beautiful language and is usually used to enhance the (beauty) of a literary work. The assumption is expressed in a specific context, by a specific person, and for a specific purpose, and is able to give an impression of an atmosphere that touches the reader's emotional power. The purpose of this research is to analyze how the style of language in the poem Siding Fakir Empunya Kata Karya Hamzah Fansuri, the approach used in this research is a qualitative method with the main data source being the poem Siding Fakir Empunya Kata Karya Hamzah Fansuri. The data collection technique used in this research is a literature study. The results of this research in the Poems of the Fakir Sessions Empunya Kata Karya Hamzah Fansuri there are four language styles, namely Hyperbole, Simile, Personification and Metaphor.